2019
DOI: 10.56093/ijas.v89i1.86098
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of quality attributes and shelf-life in strawberry (Fragaria × ananassa) fruits during storage as influenced by edible coatings

Abstract: The present investigation was carried out during 2015-16 at department of Horticulture, Aromatic and Medicinal Plants, Mizoram University, Aizawl to find out suitable edible coating on prolonging shelf-life of strawberry fruits.The different treatments were: T1: coconut oil 100%, T2 : castor oil 100%, T3 : olive oil 100%, T4 : Liquid paraffin wax 100%, T5 : Aloe vera gel, T6 :chitosan (1% w/v), T7 : chitosan (2%w/v), T8 : kaolene (1%w/v), T9 : kaolene (2%w/v), T10 : carboxy methyl cellulose (CMC) (1% w/v), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…These results were in agreement with those obtained by [15,34] for mucilage and [51] for chitosan. The effect of cold storage along with the application of edible coatings on metabolic activities can reduce the consumption of organic acids during the respiration process and thus demonstrates the maintenance of TSS during cold storage [54].…”
Section: Fig (6): the Influence Of Mucilages Extracted From Some Vege...mentioning
confidence: 99%
“…These results were in agreement with those obtained by [15,34] for mucilage and [51] for chitosan. The effect of cold storage along with the application of edible coatings on metabolic activities can reduce the consumption of organic acids during the respiration process and thus demonstrates the maintenance of TSS during cold storage [54].…”
Section: Fig (6): the Influence Of Mucilages Extracted From Some Vege...mentioning
confidence: 99%
“…The increased value of TSS and lower amount of acids in control fruits exhibited higher TSS/acid ratio. Hazarika et al (2019) reported higher TSS/acid ration in coated strawberry fruits. Dang et al (2008) reported similar results in mango fruits where lower TA content in coated fruits contributed lower TSS/acid ratio.…”
Section: Resultsmentioning
confidence: 98%
“…The coating materials make lesser availability of oxygen, thus retained higher content of OA (Medeiros et al, 2012). In the treated fruits, lesser availability of oxygen and lesser oxidation preserved the acids and resulted higher TA (Hazarika et al, 2019). Previously, Gol et al (2013) and S. Ali et al (2021) reported the CMC coating, delayed senescence in fruits which might be associated with higher retention of TA.…”
Section: Resultsmentioning
confidence: 99%
“…The study was conducted in University of Agriculture, Faisalabad, Pakistan. Hazarika et al, [46] found that fruits coated with salicylic acid @ 2 mM had considerably lowest PLW after 4, 8, 12 and 16 days of storage, respectively. Also revealed that…”
Section: Effects Of Salicylic Acid Treatments On Physiological Loss I...mentioning
confidence: 99%